Analysis of antenna selection rate in bi-directional network coded multi-antenna relay - Eslamifar, Mahshad (2013)
In bi-directional multi-antenna relaying with binary network coding, antenna selection can offer the benefits of full diversity at lower complexity. However, the rate at which the antennas are switched can also contribute to the complexity of the relaying scheme. In this paper, we explore a way of reducing this switching rate and study the implications of a reduced switching compared to the optimal antenna selection scheme.